RESULTS OF THE ARC AND ASCENDING AORTA PROSTHETIC REPLACEMENT UNDER DIFFERENT BRAIN PROTECTION CONDITIONS - O. V. Kamenskaya (Российский кардиологический журнал, 2016)
Aim. To evaluate the results of prosthetic replacement of ascending aorta and the arc, according to the methods of brain protection.Material and methods. Totally, 63 patients included, 52 (42-60) year old with DeBakey type I chronic dissection. Group 1 (n=32) — with the method of antegrade brain perfusion (AP) within artificial circulation (AC) and hypothermia (23-24º C); group 2 (n=31) with retrograde perfusion (RP) within AC and profound hypothermia (18º C). With the cerebral oxymetry the frontal lobe oxygen supply was measured (rSO2, %) during the operation. Questionnaire SF-36 was in use for life quality assessment before and late after operation.Results. In the group 1 the rSO2 during AC reduced less than 10% from baseline, and in the group 2 values of rSO2 reduced by more than 30%, (p<0,05). Neurological complications in group 1 were registered in 12,5% cases, in the group 2 — in 35,4% (p<0,05). Logistic regression showed that decrease of rSO2 during AC for more than 33% from baseline does raise the odds for neurological disorders development 5 times. Mental health parameter (MH) in long-term follow-up of operation was negatively correlated with the duration of AC (r=-0,46; p=0,003).Conclusion. Antegrade perfusion of the brain under conditions of moderate hypothermia during reconstruction surgery of proxymal aorta demonstrated better cerebroprotection, which was showed by lower rate of neurological complications in early post-operation period comparing to patients after systemic hypothermic AC.